PERTUMBUHAN SEMAI Rhizophora mucronata lamk. PADA KOMPOSISI JENIS MANGROVE DAN LEBAR SALURAN OUTLET YANG BERBEDA DI TAMBAK WANAMINA KELURAHAN MANGUNHARJO, SEMARANG. - Nuzula Muharrahmi; Rini Budi Hastuti; Endah Dwi Hastuti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Mangrove or commonly referred to as mangrove coastal areas generally live in tropical and sub-tropical. The mangrove forest is an important area for maintaining environmental quality. The existence of mangrove forests in Indonesia is increasingly alarming due to the conversion of mangrove vegetation. One of the mangrove vegetation has undergone over the function in Indonesia is in the Village of Mangunharjo, Tugu subdistrict, Semarang. This area has a lot of experience over the land which was originally a mangrove forest vegetation community is then used as aquaculture area, residential and industrial areas. This study aims to assess the level of seedling growth of R. mucronata Lamk. in mangrove type composition and the width of outlet channel which is different in silvofishery. This research used experimental method with Randomized Design (RBD). Seedlings planted in pond (silvofishery) on a single mangrove species composition and mix as well as the width of outlet channel which is different. Data obtained in the form of average height and diameter growth of seedlings R. mucronata Lamk. Data were analyzed using analysis of variance (ANOVA). The results showed that mangrove type composition and the width of outlet channel which is different on seedling growth of R. mucronata Lamk. were not significantly different.Keywords: mangrove, silvofishery, vegetation, outlet